Awareness of risk factors and warning symptoms and attitude towards gastric cancer screening among the general public in China: a cross-sectional study. Issue 7 (23rd July 2019) - Liu, Qi; Zeng, Xi; Wang, Wen; Huang, Ruo-lin; Huang, Yan-jin; Liu, Shan; Huang, Ying-hui; Wang, Ying-xin; Fang, Qing-hong; He, Guoping; Zeng, Ying
Abstract : Objectives: This study aimed to assess the knowledge of risk factors and warning symptoms and attitude towards gastric cancer screening among the general population in China. Setting: Hunan province, China Participants: Individuals aged older than 18 years were recruited using a cluster sampling method. Design: A cross-sectional study, and a pretested structured questionnaire was used to assess participants' awareness of gastric cancer. Primary and secondary outcome measures: Knowledge level of risk factors and warning symptoms of gastric cancer, gastric cancer screening attitude, sociodemographic factors associated with gastric cancer knowledge and screening behaviour. Results: This study comprised 1200 participants with a mean age of 40.31 (SD 16.73) years, of whom 622 (51.8%) were women. The mean score for gastric cancer knowledge was 8.85/22 (SD 6.48). There were 47.0% of the participants who had a low knowledge level about the risk factors and warning symptoms of gastric cancer. In total, 83.8% believed screening is helpful for early detection of gastric cancer, and 15.2% had undergone gastric cancer screening. The most common reason for not undergoing screening was having 'no symptoms' (63.0%), followed by 'fear of undergoing gastroscopy' (38.1%). Independent factors related to lower knowledge levels included male sex, living in rural areas, lower educational level, working as a farmer and without a family history of gastric cancer (p<0.05). Factors independently associated with screening behaviour included white-collar employment, higher income and having upper gastrointestinal tract diseases (p<0.05). Conclusions: In China, people have poor knowledge about risk factors and warning symptoms of gastric cancer, but a majority have a positive attitude towards the benefits of gastric cancer screening. Being asymptomatic and having a fear of gastroscopy were the main self-reported reasons for not undergoing screening. These results highlight the urgent need for educational campaigns to improve gastric cancer awareness.